Computerized clinical documentation system in the pediatric intensive care unit - Menke, James A (BioMed Central, 2001)
BACKGROUND: To determine whether a computerized clinical documentation system (CDS): 1) decreased time spent charting and increased time spent in patient care; 2) decreased medication errors; 3) improved clinical decision making; 4) improved quality of documentation; and/or 5) improved shift to shift nursing continuity. METHODS: Before and after implementation of CDS, a time study involving nursing care, medication delivery, and normalization of serum calcium and potassium values was performed. In addition, an evaluation of completeness of documentation and a clinician survey of shift to shift reporting were also completed. This was a modified one group, pretest-posttest design. RESULTS: With the CDS there was: improved legibility and completeness of documentation, data with better accessibility and accuracy, no change in time spent in direct patient care or charting by nursing staff. Incidental observations from the study included improved management functions of our nurse manager; improved JCAHO documentation compliance; timely access to clinical data (labs, vitals, etc); a decrease in time and resource use for audits; improved reimbursement because of the ability to reconstruct lost charts; limited human data entry by automatic data logging; eliminated costs of printing forms. CDS cost was reasonable. CONCLUSIONS: When compared to a paper chart, the CDS provided a more legible, compete, and accessible patient record without affecting time spent in direct patient care. The availability of the CDS improved shift to shift reporting. Other observations showed that the CDS improved management capabilities; helped physicians deliver care; improved reimbursement; limited data entry errors; and reduced costs.